Research in law and economics a journal of policy - Zerbe, Richard O.; Kirkwood, John B. (Emerald, 2007)
Written by leading experts in the field, each chapter in this book examines in depth a topic in law and economics. John Connor begins by describing and evaluating the results of his extensive survey of reports of cartel overcharges. Dennis Weisman models the price effects of mergers that not only increase concentration in the relevant market but also increase the merged firms' participation in other, complementary markets. Malcolm Coate and Mark Williams develop a superior method for calculating critical loss in markets that are relatively homogenous and competitive premerger. Zhiqi Chen surveys recent developments in economic theories of buyer power and creates a general framework for antitrust analysis. Finally Thomas J. Miceli and Kathern Segerson, given the difficulty of collecting damages after a long latency period, examine the desirability of granting toxic exposure victims an independent cause of action for medical monitoring at the time of exposure. They show that such a cause of action increase incentives for injurer care but only at the cost of greater litigation cost and the reluctance of courts to adopt such a proposed cause of action reflect their awareness of this trade-off.
Keywords: Law -- General.; Business & Economics -- Economics -- General.; Jurisprudence & philosophy of law.; Economic theory & philosophy.; Trade regulation -- United States.; elektronické knihy; electronic books